Modified NCM811 precursor as well as preparation method and application thereof
By using sodium sulfamate as an interface activator in the coprecipitation reaction, the lattice parameters of the NCM811 precursor are regulated, and the problem of degradation of the cycle stability of nickel-rich positive electrode materials is solved, and efficient cycle stability and discharge capacity are achieved. Provides a basis for further modification.
Patent Information
- Application Number
- CN202411280066.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-27
AI Technical Summary
As the proportion of nickel elements increases, the cyclic stability of nickel-rich NCM811 positive electrode material decreases, and the concentration of lattice defects increases. Existing modification strategies such as coating coating can isolate the intrusion of electrolyte, but lead to capacity and rate performance. loss.
By using sodium sulfamate as an interface activator in the co-precipitation reaction, the pH value and temperature are controlled, and the lattice parameters of the NCM811 precursor are precisely regulated, the asymmetric mixing of lithium ions and nickel ions are reduced, and the circulation of materials is improved. stability.
The cycle stability and discharge capacity of NCM811 have been significantly improved. The capacity retention rate has been increased by about 20% after 300 cycles, and the remaining capacity has been increased by about 40mAh g-1. At the same time, the introduction of non-main phase elements is avoided, providing a joint force of further modification strategies. Basic use.
Smart Images

Figure CN119191381A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy and chemical engineering, and specifically relates to a modified NCM811 precursor and a preparation method and application thereof. Background Art
[0002] The rapid popularization of electric vehicles and hybrid electric vehicles has promoted the development of lithium-ion batteries, making it one of the most critical energy storage technologies today. Among them, lithium nickel cobalt manganese oxide positive electrode material, that is, a mixture of three transition metals Ni / Co / Mn, as one of the mainstream positive electrode solutions, has the advantages of high energy density, long cycle life, low cost and good safety. By increasing the proportion of nickel in NCM ternary materials, the capacity of the battery can be significantly improved and the production cost can be reduced. For example, LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) can provide about 200 mAh g at 4.3 V cutoff voltage -1 discharge capacity. However, with the increase of the proportion of nickel in the ternary positive electrode, the problems of reduced cycle stability and increased lattice defect concentration of nickel-rich NCM become prominent. Although modification strategies such as coating can isolate the electrolyte from the intrusion and damage to the material structure by building a protective layer and maintain the stability of the material structure, the sacrifice in capacity and rate performance cannot be ignored. Therefore, it is very necessary to develop a method to solve the above technical problems. Summary of the invention
[0003] The first purpose of the present invention is to provide a modified NCM811 precursor; the second purpose is to provide a method for preparing the NCM811 precursor; and the third purpose is to provide an application of the NCM811 precursor.
[0004] The first object of the present invention is achieved in that the modified NCM811 precursor is prepared by complexation-coprecipitation reaction using transition metal salt solution as raw material, NaOH as precipitant, NH4OH as complexing agent, and sodium aminosulfonate as interfacial activator.
[0005] The second object of the present invention is achieved by using deionized water as the base liquid, adding sodium sulfamate, controlling the temperature at 40-60° C. under a nitrogen atmosphere, adding sodium hydroxide solution to adjust the pH value to 11-12, and simultaneously adding a transition metal salt solution and an ammonia solution to react. After the reaction is completed, the target modified NCM811 precursor is obtained by filtering, washing and drying.
[0006] The specific operations are as follows: Add deionized water as the base liquid to the reactor, add 0.1-2 mol% sodium sulfamate, stir until dissolved, and then pass N2 to purge the air in the reactor. Then raise the temperature to 40-60 ℃, and pump in 6-10 M NaOH solution to adjust the pH value in the reactor to a constant range of 11-12. After the temperature and pH value are stable, add 1-2 mol L -1 The transition metal salt solution was stirred at a rate of 0.5-5 ml min -1 The feed rate is pumped into the kettle, and the ammonia solution as a complexing agent is pumped into the kettle at a rate of 0.05-1 ml min according to the concentration of the salt solution and the feed rate. -1 The feed rate of the NaOH solution is pumped in synchronously, and the pH total dynamic control system automatically adjusts the feed rate of the NaOH solution to maintain the pH fluctuation in the kettle below ±0.1. After the feed liquid is pumped in, the reaction is continued for 4 to 12 hours to mature the precursor particles. The precursor powder is obtained after filtration, washing and drying.
[0007] The technical principle is: The coprecipitation reaction of the precursor is completed in two main steps using transition metal salt solution as raw material, NaOH as precipitant, NH4OH as complexing agent, and sodium aminosulfonate as interfacial activator. In the first step, the transition metal ion (TM refers to Ni 2+ 、Co 2+ , Mn 2+ ) forms an ammonia complex with NH3 in the solution (Formula 1). Then, in the second step, the hydroxide ion (OH - ) replaces the ammonium ion in the complex, reacts and forms a transition metal hydroxide precipitation core (Formula 2): TM 2+ + nNH3 → [TM(NH3) n ] 2+ (1) [TM(NH3) n ] 2+ + 2OH - → TM(OH)2+ nNH3(2) As the reaction proceeds, the precipitates aggregate around the core and gradually form primary particles. When their particle size exceeds a certain threshold, the growth of these primary particles stagnates and they begin to gradually aggregate to form secondary particles. The size of the particles begins to increase until they reach a critical value and stop growing.
[0008] In this process, the aminosulfonate in the solution, through the same complexation with transition metal ions, realizes the anchoring effect based on the (001) crystal plane in the process of crystal particle growth and stacking, accurately exerts the interface activation effect on the (001) crystal plane of the precursor, realizes the interference with the stacking process and the precise regulation of the spacing in the c-axis direction, namely "anchoring complexation-interface activation". After the lattice arrangement is fixed, the complexed aminosulfonate and ammonium ions are OH - It can be replaced, but its local moderate lattice expansion effect can be retained.
[0009] The present invention uses the technology of "anchor complexation-interface activation" to precisely control the lattice parameters of the precursor during the coprecipitation stage, which reduces the level of asymmetric lithium-nickel mixing during lithium ion embedding during the sintering process, and makes the NCM811 structure more complete, thereby greatly improving the cycle stability of NCM811. It is worth noting that since the optimization effect of this technology depends on the regulation of material structure parameters rather than the introduction of other substances or structures, the modified NCM811 using this technology can be further modified by other strategies without hindrance to achieve further improvement of electrochemical performance.
[0010] The third object of the present invention is achieved by using the modified NCM811 precursor in the preparation of NCM811 positive electrode materials with lower cation mixing symmetry level and good cycle performance.
[0011] The specific operations are as follows: The precursor powder was mixed with LiOH·H2O (molar ratio Li:TM = 1-1.1:1) and ground, and then placed in a vacuum box atmosphere furnace for sintering in air or O2 atmosphere. The heating rate was set at 2-10 ℃ min -1 The first stage of sintering is kept at a constant temperature of 500-600 °C for 4-10 h, and the second stage of sintering is kept at a constant temperature of 700-800 °C for 8-16 h, followed by cooling in the furnace to obtain NCM811 positive electrode material.
[0012] The technical principle is: The components in the mixture are evenly distributed in the first constant temperature process. As the temperature rises further, lithium ions gradually embed into the oxygen-oxygen layer gap, and the nickel cobalt manganese hydroxide precursor gradually transforms into lithium nickel cobalt manganese oxide with a hexagonal layered α-NaFeO2 structure. The reactions that occur during the whole process are as follows (TM in the formula refers to transition metal Ni / Co / Mn): TM(OH)2+ LiOH·H2O + O2→ LiTMO2+ H2O What happens during the sintering process with the intercalation of Li ions is that when Li ions migrate between adjacent tetrahedrons, they will first move from the center of the tetrahedron to the edge, which will cause the Ni ions in the adjacent position to be repelled from the center of the tetrahedron where it is located to approach the next Li layer. If the corresponding position in the next layer is a vacancy that has not yet been embedded with Li ions, Ni ions will easily leave the transition metal layer and enter the Li layer, and the diffusion of Li ions within the layer is obviously easier than that between the layers, which also causes the phenomenon that the mixing degree of Ni ions in NCM811 is generally higher than that of Li ions. At the same time, the poor order of the layered structure during the preparation of the precursor is also likely to cause more Ni ions to migrate to the non-transition metal layer to play the role of supporting structure, which also leads to a significantly higher degree of mixing of Ni ions than Li ions. Therefore, under the premise of maintaining the orderly arrangement of the layered structure of the NCM811 material, the precise control of the precursor lattice parameters helps to reduce the asymmetric level of Li / Ni cation mixing. Previous studies have shown that a lower level of cation mixing is strongly correlated with good NCM811 cycle performance.
[0013] The specific process flow adopted by the present invention is as follows: NiSO4.6H2O, CoSO4.7H2O and MnSO4.H2O are dissolved in deionized water to obtain a transition metal salt solution, and the molar ratio of Ni:Co:Mn is controlled to be 8:1:1.
[0014] Prepare NaOH solution as precipitant and NH3·H2O as complexing agent for later use.
[0015] A pH meter was used to control the pH value of the entire process in the reactor to be constant.
[0016] Before the experiment, deionized water was added to the continuous stirred reactor (CSTR), and N2 was used for purging to expel the air in the reactor. An appropriate amount of sodium aminosulfonate (NH2NaSO3) was added and stirred until dissolved. The temperature was raised to the reaction temperature, and NaOH solution was pumped in to adjust the pH value to the designed value.
[0017] After the pH value and temperature are stabilized, the prepared transition metal salt solution and ammonia solution are gradually pumped into the kettle at a constant rate, and NaOH solution is used to maintain the pH value of the liquid in the kettle constant.
[0018] The reactor is operated under stirring for a period of time and then allowed to stand to allow the precursor particles to mature.
[0019] The kettle liquid was filtered and washed alternately with deionized water and ethanol for more than three times. The filter cake was dried in a blast drying oven to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2 precursor precipitation.
[0020] Then, the precursor was mixed with LiOH·H2O (prepared in a certain molar ratio) and ground, and then placed in a vacuum box atmosphere furnace for sintering.
[0021] The two-stage calcination method is used to maintain the temperature at two temperatures for a period of time, and then the furnace is naturally cooled to obtain Li(Ni 0.8 Co 0.1 Mn 0.1 )O2 positive electrode material.
[0022] The present invention introduces sodium aminosulfonate during the coprecipitation process and uses the strategy of "anchor complexation-interface activation" to precisely control the lattice parameters of the NCM811 precursor, thereby reducing the level of structural defects that occur during the sintering process with the insertion of lithium ions. -1 Increased to 204mAh g -1 ), which greatly improved the cycle stability of the material. After 300 cycles, the capacity retention rate of the material was increased by about 20%, and the residual capacity was increased by about 40 mAh g -1 This method does not introduce non-main phase elements and structures into the modification of NCM811, which provides a convenient basis for its combined use with other modification strategies. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the process flow of the present invention; Figure 2 Schematic diagram of the comparison of XRD patterns of the modified NCM811 precursor (N-pre) and the control sample (S-pre); Figure 3 Schematic diagram of the SEM image comparison of the modified NCM811 precursor (N-pre) and the control sample (S-pre); Among them, a is the modified NCM811 precursor (N-pre); b is the control sample (S-pre); Figure 4 Schematic diagram of the comparison of XRD patterns of modified NCM811 (N) and control sample (S); Figure 5 Schematic diagram of the SEM image comparison of modified NCM811 (N) and control sample (S); Figure 6 Schematic diagram of the comparison of charge and discharge curves of modified NCM811 (N) and control sample (S); Figure 7 Schematic diagram of the comparison of cyclic stability tests of modified NCM811 (N) and control sample (S). DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited in any way. Any changes or substitutions made based on the teachings of the present invention belong to the protection scope of the present invention.
[0025] The modified NCM811 precursor of the present invention is prepared by complexation-coprecipitation reaction using transition metal salt solution as raw material, NaOH as precipitant, NH4OH as complexing agent and sodium aminosulfonate as interfacial activator.
[0026] The preparation method of the modified NCM811 precursor of the present invention is to use deionized water as the base liquid, add sodium sulfamate, control the temperature at 40-60° C. under a nitrogen atmosphere, add a sodium hydroxide solution to adjust the pH value to 11-12, and simultaneously add a transition metal salt solution and an ammonia solution to react. After the reaction is completed, the target modified NCM811 precursor is obtained after filtering, washing and drying.
[0027] The transition metal salt solution is a nickel-cobalt-manganese salt solution.
[0028] The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese salt solution is (6-10): (0.5-1.5): (0.5-1.5).
[0029] The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese salt solution is 8:1:1.
[0030] The reaction time is 4 to 12 hours.
[0031] During the reaction, the pH control system automatically adjusts the feeding rate of the NaOH solution to maintain the pH value at 11-12 with a fluctuation less than ±0.1.
[0032] The application of the modified NCM811 precursor described in the present invention is the application of the modified NCM811 precursor in the preparation of NCM811 positive electrode materials with lower cation mixing symmetry level and good cycle performance.
[0033] The modified NCM811 precursor is used to prepare the NCM811 positive electrode material with a lower cation mixing symmetry level and good cycle performance. LiOH·H2O is added to the modified NCM811 precursor, mixed and ground, and then sintered in air or oxygen atmosphere to obtain the NCM811 positive electrode material.
[0034] The sintering is performed by setting the heating rate to 2-10°C / min; the first stage of sintering is maintained at a constant temperature of 500-600°C for 4-10 hours; the second stage of sintering is maintained at a constant temperature of 700-800°C for 8-16 hours, and then the target NCM811 positive electrode material is obtained by cooling the furnace.
[0035] The present invention is further described below with specific implementation cases: Example 1 Complexation-coprecipitation stage: AR-grade NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were dissolved in deionized water to prepare 1.5L transition metal salt solution with a transition metal ion concentration of 2 mol L -1 ; Prepare 10 mol L -1 NaOH solution was used as a precipitant; 250 ml of commercial ammonia water was added to 50 ml of deionized water as a complexing agent; 1 mol% of sodium sulfamate was weighed as an interfacial activator. 1.5 L of deionized water was added to a 5 L reactor as a base liquid, and all the sodium sulfamate was added to the base liquid. The stirring and N2 purge of the reactor were turned on. After the sodium sulfamate was completely dissolved, the reactor was heated to 55 °C and NaOH solution was pumped in to adjust the pH of the base liquid to 11.8. After the temperature and pH value were stable, the reaction mixture was stirred at 1 ml min -1 and 0.2 ml min -1 The transition metal salt solution and the complexing agent were pumped in synchronously at a feed rate of , and the feed rate of the precipitant was controlled by a pH meter. After all the feed solutions were pumped in, the reaction continued for 8 hours. It was then filtered and washed, and dried at 120 °C for 12 hours to obtain a modified precursor, which was labeled as N-pre (the control experimental group without the addition of surfactant was labeled as S-pre). The XRD, SEM, and ICP-MS characterization comparison results of the precursor are shown in Figure 2. Figure 2 , Figure 3 shown.
[0036] Content of non-main phase residual elements in precursor samples (ICP-MS) .
[0037] Sintering-oxidation stage: 10 g of the precursor and 4.73 g of LiOH·H2O were weighed, ground and mixed evenly, and then placed in a vacuum box atmosphere furnace and heated at 5 °C min -1 The temperature was raised to 500 °C at a heating rate and kept constant for 6 h, then continued to rise to 750 °C and kept constant for 12 h, and then cooled in the furnace to obtain the active material NCM811. The interface activation modification group and the control group are marked as N and S, respectively. The structural morphology characterization comparison results of the active materials are shown in Figure 4 , Figure 5 shown.
[0038] Comparison of the content ratio of main phase elements (ICP-OES) .
[0039] The electrochemical performance test was carried out using a CR2032 half-cell. The positive electrode slurry was prepared by dissolving and mixing 10 wt% polyvinylidene fluoride (PVDF), 10 wt% Super P and 80 wt% active material in N-methylpyrrolidone (NMP) to prepare a slurry. After the slurry was stirred evenly, it was coated on an aluminum foil (28±1 μm) with a thickness of 300 μm, and then dried at 80 °C for 1 h. After the NMP on the surface of the electrode was volatilized, it was moved to a vacuum drying oven and dried at 120 °C for 24 h. The dried electrode was rolled to a thickness of 70 μm, and the electrode sheet with a diameter of 14 mm obtained by slicing was transferred to a glove box filled with argon to ensure that the concentrations of H2O and O2 were maintained below 0.1 ppm. Metal lithium sheet was used as the counter electrode, Celgard 2400 as the separator, EC:DEC solution (volume ratio of 1:1) containing 1M LiPF6 as the electrolyte, CR2032 half-cell was assembled and sealed in the glove box. To ensure data accuracy, the active material loading in all batteries was kept at 18.0±0.4 mg. The electrochemical performance was evaluated using the Blue Battery Test System in the voltage range of 2.8 V to 4.3 V. Before the test, it was first allowed to stand at room temperature for 12 h to ensure that the electrolyte fully wetted the electrode, and the current density was set to 1C=200 mA g -1 (vs. Li / Li+).
[0040] like Figure 6 As shown in Figure 2, at a charge and discharge rate of 0.1C, the discharge capacity of the modified NCM811 reached 203.1 mAh g -1 , which is improved compared with the control samples.
[0041] Carry out 300 charge and discharge cycles at 1C rate. Figure 7 As shown in Figure 2, after 300 cycles, the modified sample N has a capacity of 111.47 mAh g -1 The discharge capacity is about 40 mAh g higher than that of the control sample S. -1 The capacity retention rate of modified sample N is 60.27%, which is nearly 20% higher than that of control sample S. The Coulombic efficiency of control sample S shows obvious decay after 300 cycles, which is only 93.9%. In contrast, the Coulombic efficiency of modified sample N remains at 98.09% after 300 cycles, with limited decay, which verifies the electrochemical stability of modified NCM811 in long-term charge and discharge cycles, indicating that modified sample N has successfully achieved a significant improvement in the cycle stability of NCM811 without losing capacity.
Claims
1. A modified NCM811 precursor, characterized in that: The modified NCM811 precursor is prepared by complexation-coprecipitation reaction using transition metal salt solution as raw material, NaOH as precipitant, NH4OH as complexing agent and sodium aminosulfonate as interfacial activator.
2. A method for preparing the modified NCM811 precursor according to claim 1, characterized in that: Deionized water is used as the base liquid, sodium aminosulfonate is added, and under a nitrogen atmosphere, the temperature is controlled at 40-60°C, sodium hydroxide solution is added to adjust the pH value to 11-12, and transition metal salt solution and ammonia solution are simultaneously added to react. After the reaction is completed, the target modified NCM811 precursor is obtained after filtering, washing and drying.
3. The preparation method according to claim 2, characterized in that: The transition metal salt solution is a nickel-cobalt-manganese salt solution.
4. The preparation method according to claim 3, characterized in that: The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese salt solution is (6-10): (0.5-1.5): (0.5-1.5).
5. The preparation method according to claim 2 or 3, characterized in that: The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese salt solution is 8:1:
1.
6. The preparation method according to claim 2, characterized in that: The reaction time is 4 to 12 hours.
7. The preparation method according to claim 2, characterized in that: During the reaction, the pH control system automatically adjusts the feeding rate of the NaOH solution to maintain the pH value at 11-12 with a fluctuation less than ±0.
1.
8. An application of the modified NCM811 precursor according to claim 1, characterized in that: The modified NCM811 precursor is used in preparing NCM811 positive electrode materials with lower cation mixing symmetry level and good cycle performance.
9. The use according to claim 8, characterized in that: The modified NCM811 precursor is used to prepare the NCM811 positive electrode material with a lower cation mixing symmetry level and good cycle performance. LiOH·H2O is added to the modified NCM811 precursor, mixed and ground, and then sintered in air or oxygen atmosphere to obtain the NCM811 positive electrode material.
10. The use according to claim 9, characterized in that: The sintering is performed at a heating rate of 2-10°C / min; the first stage of sintering is performed at a constant temperature of 500-600°C for 4-10 hours; The second stage of sintering is to maintain a constant temperature of 700~800℃ for 8~16h, and then cool the furnace to obtain the target NCM811 positive electrode material.
